2020
DOI: 10.1007/s41403-020-00153-3
|View full text |Cite
|
Sign up to set email alerts
|

Fight Against COVID-19: ARCI’s Technologies for Disinfection

Abstract: COVID-19 (SARS-CoV-2) is causing a huge concern to the global population due to its highly contagious properties. The SARS-CoV-2 is a new variant in the coronavirus family. The world is focussing on several methods to battle against this novel corona virus, including control of its spread. In this context, ARCI has quickly made efforts to develop disinfection systems including a UVC-based disinfection trolley, honeycomb air heater and a fogging chamber using UVC germicidal lamps, dry heat sterilization and HOC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 17 publications
0
20
0
1
Order By: Relevance
“… Ludwig-Begall et al (2020) studied three techniques of decontaminating face masks: (1) ultraviolet germicidal irradiation, (2) vaporized hydrogen peroxide and (3) dry heat ( Ludwig-Begall et al, 2020 ). Sarada et al (2020) described the technologies of the International Advanced Research Center for Powder Metallurgy and New Materials (ARCI), India, in developing various disinfection systems to combat COVID-19 ( Sarada et al, 2020 ). ARCI used physical, chemical and dry heat processes to disinfect surfaces effectively.…”
Section: Introductionmentioning
confidence: 99%
“… Ludwig-Begall et al (2020) studied three techniques of decontaminating face masks: (1) ultraviolet germicidal irradiation, (2) vaporized hydrogen peroxide and (3) dry heat ( Ludwig-Begall et al, 2020 ). Sarada et al (2020) described the technologies of the International Advanced Research Center for Powder Metallurgy and New Materials (ARCI), India, in developing various disinfection systems to combat COVID-19 ( Sarada et al, 2020 ). ARCI used physical, chemical and dry heat processes to disinfect surfaces effectively.…”
Section: Introductionmentioning
confidence: 99%
“…The precise timing, the location, and the mechanism of disinfection, the type of disinfectant to be used, and safety measures to be implemented for both public health and the environment must be determined (Iyiola et al 2020 ; Nabi et al 2020 ; Zhang et al 2020 ). Determination of the minimum amount of disinfectant necessary, appropriate exposure levels, and appropriate level of contact is essential for optimum action (Sarada et al 2020 ). Avoidance of indiscriminate sprays, minimization of public movement, and the development of low-risk or nontoxic but effective disinfectants for future safe applications should be an international priority (Iyiola et al 2020 ; Nabi et al 2020 ; Zhang et al 2020 ).…”
Section: Updated Disinfection Approaches Against Sars-cov-2mentioning
confidence: 99%
“…Avoidance of indiscriminate sprays, minimization of public movement, and the development of low-risk or nontoxic but effective disinfectants for future safe applications should be an international priority (Iyiola et al 2020 ; Nabi et al 2020 ; Zhang et al 2020 ). Additionally, efforts should be engaged for the development of disinfection systems, such as UVC-based disinfection trolleys, UVC germicidal lamp-based fogging chambers, dry heat sterilization, and HOCl-based chemical disinfectants (Sarada et al 2020 ).…”
Section: Updated Disinfection Approaches Against Sars-cov-2mentioning
confidence: 99%
“…EW at HOCl concentration of 200 ppm is effective in inactivating a variety of viruses, including coronaviruses, noroviruses, and other enteric viruses (15). Recent studies (4,15,23) reported the effectiveness of EW with HOCl concentrations as low as 100 ppm against SARS-CoV-2, and many HOCl-based products have been developed that meet the EPA criteria for use against SARS-CoV-2 (5). Moreover, previous studies (24,25) showed that slightly acidic EW and neutral EW generated in single-cell units (without diaphragm), similar to that mentioned in this report, were effective against difficult-to-kill viruses/pathogens (such as non-enveloped viruses (e.g., norovirus) (26).…”
Section: Reportmentioning
confidence: 99%